Corner of Frederick Street and Marine Square, Trinidad - (:unkn) unknown (My University, 2010)
An aerial view of the corner of Frederick Street and Marine Square which was renamed Independence Square in 1961. A tramcar can be seen at the bottom of Frederick Street and on either side of the street are two major retail stores Maillards and Salvatori Scott and Company.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Streets--Trinidad and Tobago; Stores, retail--Trinidad and Tobago; General stores--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; 1923; Frederick Street (Port of Spain); Marine Square (Port of Spain); Independence Square (Port of Spain)